2012
DOI: 10.1248/cpb.60.260
|View full text |Cite
|
Sign up to set email alerts
|

Release Profiles of Dexamethasone Dipropionate from Admixtures of Steroid and Heparinoid Ointments Prepared by Different Mixing Methods

Abstract: Characterization and release profiles of commercial dexamethasone dipropionate (DDP) from an innovator and 2 generic ointments (Methaderm (IM), Promethasone (GP), and Mainvate (GM)) and their admixtures with heparinoid ointment (Hirudoid Soft) were investigated. The admixtures were prepared using 2 mixing methods (slab or rotation/revolution mixer). Microscopic and FT-Raman spectrometric analyses revealed that the ointments, except for IM, contained DDP crystals. A silicone membrane was used for the evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…In older patients, however, topical treatment with the use of multiple external drugs may become difficult because of patients' lower self-care ability. Therefore, to improve adherence to external treatment in older patients with AD, it is sometimes necessary to prescribe topical corticosteroids and moisturizers as an admixed preparation, although the medicinal properties and stability of the drugs may be somewhat unstable [56].…”
Section: Topical Corticosteroidsmentioning
confidence: 99%
“…In older patients, however, topical treatment with the use of multiple external drugs may become difficult because of patients' lower self-care ability. Therefore, to improve adherence to external treatment in older patients with AD, it is sometimes necessary to prescribe topical corticosteroids and moisturizers as an admixed preparation, although the medicinal properties and stability of the drugs may be somewhat unstable [56].…”
Section: Topical Corticosteroidsmentioning
confidence: 99%
“…A number of other studies found significant destabilization of the mixed preparations (e.g., phase separation into distinct layers and bleeding of oil components). 1,3,13,14) In the present study, we focused on the compatibility of moisturizing creams with an ointment base. We tested various commercial creams that are popularly used in Japan.…”
Section: H-nmr Spectra Of Each Phase-separated Layer Acquired From Thmentioning
confidence: 99%
“…The mixing operation is aimed at improving patient compliance; the admixture allows the patients to reduce the frequency of application and modify the sticky and uncomfortable texture of the ointment base. [1][2][3][4][5] For the mixing operation, a centrifuge-type apparatus called "a revolution/rotation" hybrid mixer is widely used in pharmacy. 6) This apparatus comprises a main rotary head mounted on a vertical axis for the rotation motion and a secondary rotor mounted in bearings on the main head for the revolution motion.…”
mentioning
confidence: 99%